Stock Market Liquidity and the Macroeconomy : Evidence from Japan - Choi, Woon.; Cook, David (Washington, D.C. : International Monetary Fund, 2005)
In a liquid financial market, investors are able to sell large blocks of assets without substantially changing the price. We document a steep drop in the liquidity of the Japanese stock market in the post-bubble period and a steep rise in liquidity risk. We find that, during Japan's deflationary period, firms with more liquid balance sheets were less exposed to stock market liquidity risk, while slowly growing firms were highly exposed to liquidity shocks. Also, aggregate liquidity had macroeconomic effects on aggregate demand through its effect on money demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet